Analisis Struktur dan Diksi Teks Prosedur Siswa Kelas VII SMP Negeri 43 Padang - Amanda, Deby Willy; Tamsin, Andria Catri (Journal of Education Language and Innovation, 2023)
The purpose of this research is to describe the structure and diction in the text of the seventh-grade students of SMP Negeri 43 Padang. This is qualitative research using descriptive methods. The data are the structure and diction in the procedural text of class VII students of SMP Negeri 43 Padang. The source of the data is written procedure text for class VII students of SMP Negeri 43 Padang. The results show the students have written down the five structural text procedures. Of 30 procedure texts, 27 procedure texts have an appropriate title structure, and 3 procedure texts have an inappropriate title structure. Of 29 procedure texts, 9 texts have the right objective structure, and 20 text structures have an inappropriate purpose structure. Of 30 procedure texts 5 texts have the right structure of tools and materials, and 25 texts have the structure of tools and materials that are not right. Of 30 procedure texts, 20 texts have a proper step structure, and 10 procedure texts have an inappropriate step structure. A total of 27 procedure texts, 23 texts have an appropriate summary, and 4 texts have an inappropriate closing structure. In terms of the use of diction, there are 2,201 correct use of diction and 655 inappropriate uses of diction.